Enhancing Maternal Sensitivity and Emotional Wellbeing Through a Preventative Parent–Child Relationship Intervention in a Community Setting - King, Karen; Priddis, L.; Kane, Robert (Springer, 2014)
The aim of this applied study was to explore the outcomes of a parent–child relationship intervention for enhancing maternal sensitivity to the infant’s needs and increasing maternal emotional wellbeing in the parenting situation. Whilst there is extensive support established for interventions with high-risk and at-risk populations, there is limited evidence from programs that target low risk parents who on presentation are often identified to have symptoms of depression, anxiety, or stress. A mixed methods research design was utilised to present quantitative and qualitative outcomes at pre- and post-intervention from 14 participants in the Tuned In Parenting program at a community health organisation. Self-report measures were summarised to provide a descriptive profile of participants. Recorded mother–child semi-structured play interactions were analysed using a behaviour rating scale. Transcripts of audio recordings from semi-structured interviews were analysed using a thematic and content approach. Participants demonstrated enhanced maternal sensitive responsiveness and a reduction in symptoms of maternal depression following program completion. The preventative relationship based intervention holds considerable promise in improving maternal wellbeing and transforming relationships between mothers and their children.